Convergence in comparable almost periodic reaction-diffusion systems with Dirichlet boundary conditions - Feng Cao; Yelai Fu (Electronic Journal of Differential Equations, 2014)
In this article, we study the asymptotic dynamics in nonmonotone comparable almost periodic reaction-diffusion systems with Dirichlet boundary condition, which are comparable with uniformly stable strongly order-preserving system. By appealing to the theory of skew-product semiflows, we obtain the asymptotic almost periodicity of uniformly stable solutions to the comparable reaction-diffusion system.